2017
DOI: 10.21048/ijnd.2017.54.2.14899
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practices and Nutritional Status of Children Aged One to Five Years in Jaffna District, Sri Lanka

Abstract: Breastfeeding is essential to break the vicious cycle of under nutrition of children. This study was aimed to assess the breastfeeding practices and nutritional status of children aged one to five years in Jaffna district. The study design was descriptive cross sectional. Height, weight, haemoglobin, albumin and serum ferritin of children were measured. Structured interviewer administered questionnaire was used to obtain socio-demographic factors, breastfeeding practices and dietary pattern. Among the total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
4
1
1
Order By: Relevance
“…This low rate of exclusivity of BF noticed in this part of Africa is not surprising as it is in compliance with previous studies which revealed low rates of EBF (39%) in Africa (Cai et al, 2012), and this accounts partly for the high rate of infectious diseases such as diarrhea and pneumonia among under five children in this continent (Victora et al, 2016). Higher rates of EBF (63.9%) have been observed in Jaffna District, Sri Lanka (Karthigesu et al, 2017).…”
Section: Exclusive Breastfeedingsupporting
confidence: 88%
See 1 more Smart Citation
“…This low rate of exclusivity of BF noticed in this part of Africa is not surprising as it is in compliance with previous studies which revealed low rates of EBF (39%) in Africa (Cai et al, 2012), and this accounts partly for the high rate of infectious diseases such as diarrhea and pneumonia among under five children in this continent (Victora et al, 2016). Higher rates of EBF (63.9%) have been observed in Jaffna District, Sri Lanka (Karthigesu et al, 2017).…”
Section: Exclusive Breastfeedingsupporting
confidence: 88%
“…As shown in (Mananga et al, 2014). This finding is not in accordance with the results reported by Karthigesu, Sandrasegarampillai, and Vasanthy Arasaratnam (2017) in Jaffna District, Sri Lanka, where 56.4% of children were breastfed for more than 2 years. A higher percentage (97.8%) of BF duration up to two years and above was reported in the southwest region of Bangladesh (Islam et al, 2013).…”
Section: Duration Of Breastfeedingkcontrasting
confidence: 66%
“…This study shows that the prevalence of EBF up to six months among the rural mothers was 71.2% based on “recall since birth”. It was previously reported that the prevalence of EBF until six months was 64.4% in Jaffna District [ 12 ]. The demographic and health survey (DHS) of Sri Lanka reported that the prevalence of EBF was 82%, but it was difficult to relate the DHS survey results with this study as DHS had obtained the data by a “24-h recall”, which can easily be an overestimation [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the standard of living and health facilities of rural mothers of developing countries are low. Our previous study has shown that the prevalence of malnutrition was high in rural Jaffna [ 12 ]. The causes could be multifactorial, including the low rate of EBF.…”
Section: Introductionmentioning
confidence: 99%
“…), living in hilly areas, co-existence of micronutrient deficiencies, deprived socio-economic status of families, low maternal education, age, and sex of the child are associated with the ID [22,23]. Previously, it was reported that the children from Jaffna District were considerably malnourished [24] and were with low food security [25]. A study conducted among the pregnant mothers in Jaffna District revealed that 65.1% of mothers had ID [26].…”
Section: Introductionmentioning
confidence: 99%